PRESSURE INJURY PATIENTS CHARACTERISTIC IN SOUTH EAST INDONESIA WARRANTS IMMEDIATE INITIATION OF PREDICTIVE ASSESSMENT TOOLS: A CHART REVIEW - Djunaedi, Angela; Robertus Arian Datusanantyo (Universitas Airlangga, 2025)
Highlights: 1. The absence of Stage 1 pressure injuries reflects the need for a predictive assessment tool.2. The majority of patients were aged 60–71 and had unstageable pressure injuries.3. The main referring departments were Internal Medicine, Cardiology, and Pulmonology. Abstract: Introduction: Pressure injury (PI) is a worldwide health problem, a burden in many aspects, and influences life quality. Every PI case would be different due to several underlying factors and conditions which hindered the prevention strategies. We share the overview of PI patients on South East Indonesia. Method: A descriptive-retrospective study with chart review approach was held to review all case of PI consulted to plastic surgery from 2021-2023. Basic demographic data was collected along with the wound area, PI stage, and referrer department. Result: PI was more frequent in Male patients insignificantly (p=0.069) developed more PI (55.13%) than female patients (44.87%). Almost half of PI case occurred in patients with more than 60 years old of age (48.71%). Most case were referred by the internal medicine, pulmology and cardiology department (43.59%) and mostly located in sacral region, (64.10%). Unstageable PI was found the most (48.72%) while no stage 1 PI was consulted. Discussion: The finding of the study existing knowledge about the risk factors for pressure injuries (PI), particularly sensory and motor impairment as well as immobility. The absence of stage 1 PI underscores the importance of a standardized predictive assessment tool to enhance early detection and intervention. Integrating routine visual inspection and palpation into the assessment process could improve the early recognition of PI. The intervention should be extended to educational program to family caregiver in discharge planning. Conclusion: PI incidence corresponds with known risk populations. Hospital leadership should implement predictive PI assessment tools and incorporate PI education into discharge planning to improve early detection and intervention.